PENERAPAN MODEL PROBLEM POSING UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK SMP - Kosasih, Usep; Shekhawati, Novia Nur; Aqilah, Nur; Sulastri, Yayu Laila; Prasetyo, Edo; Mulia, Silviani (Universitas Islam Nusantara, 2023)
The research in this thesis was based on the low ability of mathematical reasoning of students in mathematics learning. One of the alternatives which could be applied to improve the ability of mathematical reasoning of students needed an interesting learning and an independent thinking to understand subject material according to his ability by model problem posing. The method used in this research was a quasi experimental method with Nonequivalent Pretest-posttest Control Group Design. The research was conducted at one of the state junior high schools in Bandung District. Population in this research was all students of class VIII with a sample of students in class VIII-F as an experimental class and class VIII-G as a control class. The instrument used was a mathematical reasoning ability test, and observation sheet. According to the analysis result of Man-Whitney test in mathematical reasoning ability of student were obtained decisions that increasing the mathematical reasoning ability of student whose learning used problem posing model was better than student whose learning used discovery learning model.